Tyrosinase Inhibitory Activity of Methanolic Extract and Fractions from Green Seaweed Ulva lactuca - Gazali, Mohamad; Maknun, Fazidatul Lu’luil; Husni, Amir; Nurjanah, Nurjanah; Nursid, Muhammad; Hasanah, Uswatun; Zuriat, Zuriat; Syafitri, Rina (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2025)
Ulva lactuca, a widely available green seaweed, has demonstrated promising bioactivity as a tyrosinase inhibitor. This study aimed to evaluate the tyrosinase inhibitory activity of U. lactuca extracts and identify the active compounds responsible. The seaweed was extracted using methanol via maceration, followed by partitioning with hexane, chloroform, and water. Total phenolic and flavonoid contents were determined using UV-VIS spectrophotometry, and tyrosinase inhibition was assessed in vitro. Among the tested fractions, the hexane fraction exhibited the highest tyrosinase inhibitory activity with an IC50 value of 584.34 ± 35.07 µg/mL, classifying it as an active inhibitor. Although this activity was weaker than kojic acid (IC50 = 11.07 ± 0.86 µg/mL), the hexane fraction showed relatively high phenolic (11.66 ± 0.53 mg GAE/g) and flavonoid (9.75 ± 0.30 mg QE/g) contents. Gas Chromatography-Mass Spectrometry (GC-MS) analysis identified several bioactive compounds, notably 2,4-dimethoxycinnamic acid, chalcone, and derivatives such as 2,6-dihydroxybenzoic acid and phloretin. These findings highlight the potential of U. lactuca, particularly its hexane fraction, as a source of natural tyrosinase inhibitors. This opens avenues for its application in the pharmaceutical and cosmetic industries, especially in formulations targeting hyperpigmentation and skin brightening.